ISLAM IN GANTARANGKEKE: The Encounter of Cultural Identities - Sabara Nuruddin (Universitas Islam Negeri Alauddin Makassar, 2018)
This article is a study of Islamic relations and local traditions in this case is the Islamic tradition of the Gantarangkeke indigenous people, Bantaeng Regency as a locus. The research problem is how is the history of the Islamic encounter with Gantarangkeke locality and its influence on the beliefs and traditions of the Gantarangkeke people ?. This study belongs to the category of qualitative-descriptive field research, using a historical, philosophical, social, cultural, and descriptive-critical analytical approach. The local tradition of the Gantarangkeke community has grown long before Islam entered their territory. The tradition is rooted in the belief of the Patuntung religion which is the ancient belief of the pre-Islamic Gantarangkeke community. The local tradition is institutionalized at the Pajukukang traditional ceremony which is held every year and has several series of events, namely assulukang pangngajai, akkawaru, if ri pajukukang, and angnganre toballa'na. The encounter of Islam and local traditions gave birth to a model of cultural struggle in which Islam as a teaching that came from the outside and of a global nature was brought into the realm of the locality of the Gantarangkeke tradition. This then gave birth to the concept of Sallang religion as a meeting point between patuntung and Islamic beliefs. The concept of Sallang religion later became the basis for the locus and forms of the struggle of the culture. Cultural struggles enter the locus of the belief system, the socio-cultural system, and the rite system and the symbolic meaning of tradition. The cultural struggle gave birth to four forms of cultural and religious relations, namely negotiation, compromise, syncretism, and cultural acculturation. From this cultural struggle, the local culture model of Gantarangkeke was unique and unique.